Migration jumps of planets in transition discs - Rometsch, Thomas; Rodenkirch, Peter; Kley, Wilhelm; Dullemond, Cornelis (Astronomy and astrophysics, 2020)
Context. Transition discs form a special class of protoplanetary discs that are characterised by a deficiency of disc material close to the star. In a subgroup, inner holes in these discs can stretch out to a few tens of au while there is still mass accretion onto the central star observed at the same time.Aims. We analyse the proposition that this type of wide transition disc is generated by the interaction of the disc with a system of embedded planets.Methods. We performed two-dimensional hydrodynamics simulations of a flat disc. Different equations of state were used including locally isothermal models and more realistic cases that consider viscous heating, radiative cooling, and stellar heating. Two massive planets (with masses of between three and nine Jupiter masses) were embedded in the disc and their dynamical evolution due to disc-planet interaction was followed for over 100 000 yr. The simulations account for mass accretion onto the star and planets. We included models with parameters reminiscent of the system PDS 70. To assess the observability of features in our models we performed synthetic ALMA observations.Results. For systems with a more massive inner planet, there are phases where both planets migrate outward engaged in a 2:1 mean motion resonance via the Masset-Snellgrove mechanism. In sufficiently massive discs, the resulting formation of a vortex and the interaction with it can trigger rapid outward migration of the outer planet where its distance can increase by tens of au in a few thousand years. After another few thousand years, the outer planet rapidly migrates back inwards into resonance with the inner planet. We call this emerging composite phenomenon a migration jump. Outward migration and the migration jumps are accompanied by a high mass accretion rate onto the star. The synthetic images reveal numerous substructures depending on the type of dynamical behaviour.Conclusions. Our results suggest that the outward migration of two embedded planets is a prime candidate for the explanation of the observed high stellar mass accretion rate in wide transition discs. The models for PDS 70 indicate it is not currently undergoing a migration jump but might very well be in a phase of outward migration.
Gesehen am 21.12.2020